2018
DOI: 10.1016/j.psychres.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Schizotypal traits and their relation to rejection sensitivity in the general population: Their mediation by quality of life, agreeableness and neuroticism

Abstract: Schizotypal traits are a cluster of personality styles suggesting a potential liability for schizophrenia-spectrum disorders. Interpersonal schizotypal traits include cognitive disorganisation which consists of social anxiety, and introvertive anhedonia which consists of a lack of pleasure in social activities. Rejection sensitivity is evident all along this continuum. This study aimed to determine whether psychosocial quality of life (QOL), neuroticism and agreeableness mediates the relation between schizotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 71 publications
(79 reference statements)
0
14
0
Order By: Relevance
“…This suggests that higher schizotypal traits may be associated with impairment in pleasure experience and emotion expressivity. Previous research has reported a correlation between interpersonal schizotypal trait and rejection sensitivity (Premkumar, Onwumere, Betts, Kibowski, & Kuipers, 2018) and expression of interpersonal insecurity (Lemay & Clark, 2008). Meanwhile, schizotypal individuals have been shown to have biases in perception, such as exaggerated perception of emotion in facial expressions (Uono, Sato, & Toichi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that higher schizotypal traits may be associated with impairment in pleasure experience and emotion expressivity. Previous research has reported a correlation between interpersonal schizotypal trait and rejection sensitivity (Premkumar, Onwumere, Betts, Kibowski, & Kuipers, 2018) and expression of interpersonal insecurity (Lemay & Clark, 2008). Meanwhile, schizotypal individuals have been shown to have biases in perception, such as exaggerated perception of emotion in facial expressions (Uono, Sato, & Toichi, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…denoting the 75% percentile of the unusual experiences (positive schizotypy) subscale of the O-LIFE according to the scale norms (Mason and Claridge, 2006). The current sample (68%) had a higher percentage of participants with high positive schizotypy (68%) than a large healthy sample (n=318; 36%) (Premkumar et al, 2018). The current sample also had a lower percentage of participants with low positive schizotypy (12%), defined as a score below 4 denoting the 25 th percentile of positive schizotypy, than the other healthy sample mentioned above (n=318; Premkumar et al, 2018; 29%).…”
Section: Participantsmentioning
confidence: 90%
“…In a milder and non-clinical form, people have schizotypal traits which refer to personality traits in the healthy population that are similar to psychosis to some extent, but suggest vulnerability for psychosis (Barrantes-Vidal et al, 2013). Schizotypy is the overall latent personality organisation and a theoretical construct denoting this vulnerability, while schizotypal traits are its measurable facets (Premkumar et al, 2018). Positive schizotypy consists of perceptual aberrations, hallucinatory experiences and magical thinking (Mason, Claridge & Jackson, 2006), many of which increase under situations of social threat (Green & Phillips, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Disorganized schizotypy denotes social anxiety and communication disorder [52]. Disorganized schizotypy also relates to social stress [53][54][55] and social anxiety as rejection sensitivity [56]. In turn, disorganized schizotypy and social anxiety relate to poor recognition of anger [57,58].…”
Section: The Path From Disorganized Schizotypy To Depression and Aggrmentioning
confidence: 99%